Halotolerant PGPR Stenotrophomonas maltophilia BJ01 Induces Salt Tolerance by Modulating Physiology and Biochemical Activities of Arachis hypogaea - Alexander, Ankita; Singh, Vijay K.; Mishra, Avinash (Frontiers in Microbiology, 2020)
Arachis hypogaea (Peanut) is one of the most important cash crops grown for food and oil production. Salinity is a major constraint for loss of peanut productivity, and halotolerant plant growth promoting bacteria not only enhance plant-growth but also provide tolerance against salt stress. The potential of halotolerant bacterium Stenotrophomonas maltophilia BJ01 isolated from saline-soil was explored to enhance the growth of peanut plants under salt stress conditions. Interaction of S. maltophilia BJ01 enhances the growth of the peanut plants and protects photosynthetic pigments under salt stress. Lower electrolyte leakage (about 20%), lipid peroxidation (2.1 μmol g–1 Fw), proline (2.9 μg mg–1 Fw) content and H2O2 (55 μmol g–1 Fw) content were observed in plants, co-cultivated with PGPR compared to untreated plants under stress condition. The growth hormone auxin (0.4 mg g–1 Fw) and total amino acid content (0.3 mg g–1 Fw) were enhanced in plants co-cultivated with PGPR under stress conditions. Overall, these results indicate the beneficial effect of S. maltophilia BJ01 on peanut plants under salt (100 mM NaCl) stress conditions. In conclusion, bacterium S. maltophilia BJ01 could be explored further as an efficient PGPR for growing legumes especially peanuts under salt stress conditions. However, a detailed agronomic study would be needed to ascertain its commercial role.